Creative Fixation is No Laughing Matter: The Effects of Funny and Unfunny Examples on Humor Production. (24th September 2018) - Shin, Hyelim; Cotter, Katherine N.; Christensen, Alexander P.; Silvia, Paul J.
Abstract: How do people come up with humorous ideas? In creative cognition research, exposure to good examples sometimes causes fixation (people get "stuck" on the examples) but other times sparks inspiration (people's responses are more creative). The present research examined the effects of funny and unfunny examples on joke production. A sample of 175 adults read scenarios that they completed with funny responses. All participants were instructed to be funny, but before responding they read (a) funny responses as examples of good responses to emulate, (b) unfunny responses as examples of poor responses to avoid, or (c) no examples. The participants' own responses were rated for funniness and for similarity to the example responses, and response times were recorded. Reading either funny or unfunny examples, compared to no examples, caused people to come up with funnier jokes. Similarity to the examples was low in all conditions, so fixation was relatively modest, but people who saw unfunny examples spent more time coming up with their responses. Taken together, the findings support the growing literature showing that examples are often inspiring rather than constraining, and they imply that good and bad examples spark creative thought via different paths.